PENGENDALIAN HIPERTENSI DAN SENAM HIPERTENSI PADA LANSIA - Marthilda Suprayitna; Zuhratul Hajri; Melati Inayati Albayani; Henny Yolanda; Zuliardi Zuliardi; Raden Ahmad Dedy Mardani (Institut Kesehatan Yarsi Mataram, 2026)
Hypertension is a global health problem that poses a risk of cardiovascular complications such as myocardial infarction, coronary heart disease, congestive heart failure, and stroke, as well as chronic kidney disease and blindness when it affects the kidneys. Older adults are at high risk for hypertension; therefore, education is needed regarding its definition, causes, risks, complications, and management, along with an introduction to hypertension exercises as a non-pharmacological method to lower blood pressure and improve quality of life. Methods: The program was conducted in the service area of the Penimbung Community Health Center using a step-by-step educational approach involving visual and verbal instruction, followed by training and guidance on performing hypertension exercises. Results: Interactive health education increased the elderly participants’ knowledge of hypertension by 85%, while regular hypertension exercise reduced average systolic blood pressure by 10 mmHg within three months. Discussion: A step-by-step educational approach using visual and verbal methods, combined with hypertension exercise, effectively improved understanding and lowered blood pressure among the elderly, making it a practical and sustainable model for non-pharmacological intervention in primary health care